Acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface for the diagnosis of compensated liver cirrhosis - Pfeifer, Lukas; Görtz, Rüdiger; Sturm, Jörg; Wachter, David; Riener, M. O.; Schwitulla, Judith; Bernatik, T.; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2014)
To evaluate the diagnostic value of acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface, using histology as a gold standard for the diagnosis of compensated liver cirrhosis.73 patients without ascites undergoing liver biopsy were included in the study. The left and right liver lobes were examined with ARFI and high-frequency ultrasound. Liver surface irregularity was quantified using image analysis software to calculate the difference between the real surface and the approximated physiological surface through a 20 mm standardized line.There is a significant difference between cirrhotic and non-cirrhotic patients for both quantified liver surface (QLS) and ARFI (p < 0.001). The mean values for QLS of the left lobe were 0.71 ± 0.24 mm and 1.17 ± 0.80 mm, of the right lobe 0.56 ± 0.26 mm and 0.87 ± 0.26 mm for non-cirrhotic and cirrhotic patients, respectively. The mean values of ARFI measurements of the left lobe were 2.04 ± 0.76 m/s and 2.85 ± 0.81 m/s, of the right lobe 1.65 ± 0.61 m/s and 3.02 ± 0.77 m/s for non-cirrhotic and cirrhotic patients, respectively. Diagnostic accuracy (AUROC) was 0.78/0.80 for QLS and 0.77/0.91 for ARFI of the left/right lobe, respectively. ARFI of the right lobe is significantly better than ARFI of the left (p = 0.023) or QLS of the left (p = 0.025)/right (p = 0.046) lobe of the liver.Assessment of liver surface irregularity by high-frequency ultrasound (QLS) is a useful diagnostic test for the assessment of compensated liver cirrhosis. ARFI of the right liver lobe is significantly better than high-frequency ultrasound (QLS of the left/right lobe of the liver) and ARFI of the left lobe of the liver.
EVALuna2:1858

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Akt and p53 are potential mediators of reduced mammary tumor growth by Chloroquine and the mTOR inhibitor RAD001 - Löhberg, Christian; Strissel, Pamela; Dittrich, Ralf; Strick, Reiner; Dittmer, Jürgen; Dittmer, Angela; Fabry, Ben; Kalender, Willi Alfred; Koch, Thorsten; Wachter, David; Groh, Nicole; Polier, Astrid; et al. (Biochemical Pharmacology, 2012)

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, Julius; Fasching, Peter; Wunderle, Marius; Heindl, Felix; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, Marcus; Polifka, Iris; Wachter, David; et al. (Therapeutic Advances in Medical Oncology, 2020)
Background: Mammography can identify calcifications up to 50–100 μm in size as a surrogate parameter for breast cancer or ductal carcinoma in situ (DCIS). Microcalcifications measuring <50 µm are also associated with breast cancer or DCIS and are frequently not detected on mammography, although they can be detected with dark-field imaging. This study examined whether additional breast examination using X-ray dark-field imaging can increase the detection rate of calcifications. Advances in knowledge: (1) evaluation of additional modality of breast imaging; (2) specific evaluation of breast calcifications. Implications for patient care: the addition of X-ray dark-field imaging to conventional mammography could detect additional calcifications. Methods: Talbot–Lau X-ray phase–contrast imaging and X-ray dark-field imaging were used to acquire images of breast specimens. The radiation dosage with the technique is comparable with conventional mammography. Three X-ray gratings with periods of 5–10 µm between the X-ray tube and the flat-panel detector provide three different images in a single sequence: the conventional attenuation image, differential phase image, and dark-field image. The images were read by radiologists. Radiological findings were marked and examined pathologically. The results were described in a descriptive manner. Results: A total of 81 breast specimens were investigated with the two methods; 199 significant structures were processed pathologically, consisting of 123 benign and 76 malignant lesions (DCIS or invasive breast cancer). X-ray dark-field imaging identified 15 additional histologically confirmed carcinoma lesions that were visible but not declared suspicious on digital mammography alone. Another four malignant lesions that were not visible on mammography were exclusively detected with X-ray dark-field imaging. Conclusions: Adding X-ray dark-field imaging to digital mammography increases the detection rate for breast cancer and DCIS associated lesions with micrometer-sized calcifications. The use of X-ray dark-field imaging may be able to provide more accurate and detailed radiological classification of suspicious breast lesions. Adding X-ray dark-field imaging to mammography may be able to increase the detection rate and improve preoperative planning in deciding between mastectomy or breast-conserving therapy, particularly in patients with invasive lobular breast cancer.
CRIS-Team Scopus Importer:2020-09-25
Keywords: breast cancer; interferometry; mammography; microcalcifications

Association of molecular subtypes with breast cancer risk factors: a case-only analysis - Rauh, Claudia; Gaß, Paul; Heusinger, Katharina; Haeberle, Lothar; Jud, Sebastian; Hein, Alexander; Löhberg, Christian; Lux, Michael P.; Wachter, David; Heimrich, Jutta; Strehl, Johanna D.; Haller, Florian; et al. (European Journal of Cancer Prevention, 2015)
As breast cancer (BC) screening identifies many BCs with a good prognosis, which might be overdiagnosed and therefore overtreated, the identification of subgroups with a high risk for aggressive subtypes might be helpful. The aim of this case-case analysis was to investigate the association between epidemiological risk factors and molecular subtypes in a cohort of BC patients. Epidemiological risk factors for 2587 BC patients were obtained using a structured questionnaire and from the patients' charts. The histopathological information (estrogen and progesterone receptor, HER2 and Ki-67) used in the analysis was retrieved from the original pathology reports. Analyses using conditional inference regression trees were carried out on these data. The strongest influence factor on the distribution of the molecular subtypes was age at first diagnosis of BC. An influence of BMI was also identified in patients aged either more than 42 years or 49.6 years or less. Older patients aged more than 49.6 years and perimenopausal women with a BMI of 32.4 kg/m or less were most likely to develop luminal A-like BC. Young patients aged 42 years or less and perimenopausal patients with a BMI more than 32.4 kg/m more often developed triple-negative BC. The study confirmed that age at diagnosis is an important factor influencing the distribution of molecular subtypes. In the perimenopausal group, it may be postulated that BMI plays a critical role in the pathogenesis of BC, defining a subgroup that is more likely to develop triple-negative BC or luminal B-like disease and another group in which there is a more postmenopausal distribution pattern.
EVALuna2:5482

Characterization of Molecular Subtypes of Paget Disease of the Breast Using Immunohistochemistry and In Situ Hybridization - Wachter, David; wachter, peter wolf; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Riener, Marc-Oliver; Hartmann, Arndt; Strehl, Johanna D. (Archives of Pathology & Laboratory Medicine, 2018)
CONTEXT: - Paget disease of the breast, in most cases, represents intraepidermal spread of ductal carcinoma in situ. Molecular subtypes of invasive carcinoma of the breast have prognostic and therapeutic significance and show characteristic distribution. Little is known about the distribution of molecular subtypes in Paget disease of the breast. OBJECTIVES: - To examine the distribution of molecular subtypes in Paget disease of the breast and to compare them to concurrent invasive carcinoma of the breast, if present. DESIGN: - We examined 48 cases of Paget disease of the breast with immunohistochemistry and antibodies against estrogen and progesterone receptors, human epidermal growth factor receptor 2 (HER2), and Ki-67, as well as HER2 chromogenic in situ hybridization, to classify the cases into molecular subtypes. Then, we compared the results to the molecular subtypes of associated, invasive carcinoma of the breast, if present. RESULTS: - The HER2 subtype was the most common found in Paget disease of the breast, followed by the luminal B subtype and 2 cases of the triple-negative subtype. The associated, invasive carcinoma cases were most often of the luminal B subtype, followed by the HER2 subtype and the triple-negative subtype. The molecular subtype of Paget disease and invasive carcinoma was congruent in most of the cases. CONCLUSIONS: - Molecular subtypes of invasive carcinoma of the breast can already be detected in Paget disease. The distribution of molecular subtypes of Paget disease and of Paget disease-associated, invasive carcinoma differs from invasive carcinoma without associated Paget disease, with the HER2 subtype overrepresented in Paget disease and associated, invasive carcinoma and the luminal and triple-negative subtypes underrepresented.
EVALuna2:34808

Comparison of Sonography versus Digital Breast Tomosynthesis to Locate Intramammary Marker Clips - Schulz-Wendtland, Rüdiger; Dankerl, Peter; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Jud, Sebastian; Rauh, C.; Bayer, C. M.; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: This study aimed to compare the accuracy of sonography versus digital breast tomosynthesis to locate intramammary marker clips placed under ultrasound guidance. Patients and Methods: Fifty patients with suspicion of breast cancer (lesion diameter less than 2 cm [cT1]) had ultrasound-guided core needle biopsy with placement of a marker clip in the center of the tumor. Intramammary marker clips were subsequently located with both sonography and digital breast tomosynthesis. Results: Sonography detected no dislocation of intrammammary marker clips in 42 of 50 patients (84 %); dislocation was reported in 8 patients (16 %) with a maximum dislocation of 7 mm along the x-, y- or z-axis. Digital breast tomosynthesis showed accurate placement without dislocation of the intramammary marker clip in 48 patients (96 %); 2 patients (4 %) had a maximum clip dislocation of 3 mm along the x-, y- or z-axis (p < 0.05). Conclusion: The use of digital breast tomosynthesis could improve the accuracy when locating intramammary marker clips compared to sonography and could, in future, be used to complement or even completely replace sonography.
EVALuna2:6724

Correlation of histological and macroscopic findings in peritoneal endometriosis - Strehl, Johanna; Hackl, Janina; Wachter, David; Klingsiek, Peter; Burghaus, Stefanie; Renner, Stefan; Fasching, Peter; Hartmann, Arndt; Beckmann, Matthias (International Journal of Clinical and Experimental Pathology, 2014)
In the last two decades, a color based concept of disease activity in peritoneal endometriosis has been in use in the clinical context, with red lesions being considered active and black or white lesions being interpreted as less active or dormant.Our aim was to analyze 4 main color categories of peritoneal endometriosis (black, white, red and brown) in one single patient group using histomorphological and immunohistochemical methods.65 endometriosis lesions (30 black, 17 white, 11 brown, 7 red) were resected from 47 premenopausal, nulliparous women which had not received exogenous hormones for at least six months prior to the operation. Specimen workup, histomorphological analysis and immunohistochemical analysis were performed in a standardized manner.The color categories showed a broad overlap in proliferative activity and hormone receptor expression. Differences were found in lesion morphology. Adjacent stromal reaction in particular showed a marked increase from red through brown and black to white lesions. Differences were also seen in gland pattern and gland content.Lesion colors in peritoneal endometriosis seem to be determined by gland content and a varying adjacent stromal reaction and more likely reflect an aging process than different levels of disease activity.
EVALuna2:6566

Diabetes and prognosis in a breast cancer cohort - Schrauder, Michael; Fasching, Peter A.; Häberle, Lothar; Lux, Michael P.; Rauh, Claudia; Hein, Alexander; Bayer, Christian M.; Heusinger, Katharina; Hartmann, Arndt; Strehl, Johanna D.; Wachter, David; Schulz-Wendtland, Rüdiger; et al. (Journal of Cancer Research and Clinical Oncology, 2011)
Purpose: Epidemiological studies indicated that type 2 diabetes mellitus may increase breast cancer risk and mortality. The aim of this retrospective cohort study was to examine the effect of diabetes on the clinical course and the prognosis of early stage breast cancer in relation to tumour and patient characteristics. Methods: The cohort analyzed in this study consisted of 4,056 patients with invasive primary breast cancer. We compared overall survival, distant metastasis-free survival and local recurrence free survival between breast cancer patients with and without diabetes. Results: In our cohort 276 breast cancer patients (6.8%) were affected by diabetes compared to 3,780 patients (93.2%) without diabetes. Women with diabetes were significantly older, had larger tumours, and a higher rate of lymph node involvement. After a follow-up period of 5 years, stratification for age and adjustment for other prognostic factors, overall mortality following breast cancer was significantly higher in diabetic breast cancer patients (hazard ratio, HR 1.92; 95% confidence interval, CI 1.49-2.48). We found no significant differences in distant metastasis-free survival and local recurrence free survival between the two groups, but we found a slightly significant higher rate of distant metastasis in the group of patients with diabetes and oestrogen receptor negative tumours (HR 2.28; CI 1.31-3.97). Conclusion: In this study, patients with diabetes and oestrogen receptor negative breast cancer had a more than 2-fold higher risk for distant metastasis compared to patients without diabetes. Diabetes was also associated with an almost 2-fold increase in mortality within the 5 years follow-up period. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer; Cohort study; Diabetes mellitus; Distant metastasis; Local recurrence; Survival

DNA methylation outliers in normal breast tissue identify field defects that are enriched in cancer - Teschendorff, Andrew E.; Gao, Yang; Jones, Allison; Rübner, Matthias; Beckmann, Matthias; Wachter, David; Fasching, Peter; Widschwendter, Martin (Nature Communications, 2016)
Identifying molecular alterations in normal tissue adjacent to cancer is important for understanding cancer aetiology and designing preventive measures. Here we analyse the DNA methylome of 569 breast tissue samples, including 50 from cancer-free women and 84 from matched normal cancer pairs. We use statistical algorithms for dissecting intra- and inter-sample cellular heterogeneity and demonstrate that normal tissue adjacent to breast cancer is characterized by tens to thousands of epigenetic alterations. We show that their genomic distribution is non-random, being strongly enriched for binding sites of transcription factors specifying chromatin architecture. We validate the field defects in an independent cohort and demonstrate that over 30% of the alterations exhibit increased enrichment within matched cancer samples. Breast cancers highly enriched for epigenetic field defects, exhibit adverse clinical outcome. Our data support a model where clonal epigenetic reprogramming towards reduced differentiation in normal tissue is an important step in breast carcinogenesis.
EVALuna2:6810

Does stimulation with human gonadotropins and gonadotropin-releasing hormone agonist enhance and accelerate the developmental capacity of oocytes in human ovarian tissue xenografted into severe combined immunodeficient mice? - Lotz, Laura; Schneider, Heike; Hackl, Janina; Wachter, David; Hoffmann, Inge; Jurgons, Roland; Beckmann, Matthias; Dittrich, Ralf (Fertility and Sterility, 2014)
To assess the capacity of human frozen-thawed ovarian follicles matured in xenografts to form metaphase II (MII) oocytes after xenotransplantation and exogenous stimulation.Prospective controlled animal study.University hospital gynecology research unit.Ovarian fragments were obtained from 17 women with malignant diseases who wished to cryopreserve ovarian tissue for later pregnancy before chemotherapy.Eighty-eight female severe combined immunodeficient (SCID) mice.Cryopreserved human ovarian tissue was grafted into oophorectomized SCID mice. The mice were divided into three groups: Group A received hMG alone every 2 days for a maximum of 24 weeks; group B additionally received nRH agonist (GnRHa) every 4 weeks; and group C was an untreated control group.Follicular density, morphology, proliferation, oocyte maturation, malignant cell contamination.Follicle survival and development were similar in all three groups. No significant interactions between the stimulation protocols and grafting duration were noted. Three MII oocytes were observed in grafted follicles. Two MII oocytes were harvested without stimulation. None of the mice showed signs of reintroduced malignancy, nor did microscopic evaluation of the grafts raise any suspicion of residual malignant disease.After xenotransplantation, human primordial follicles can be matured to MII oocytes even without stimulation. Administering human gonadotropin and GnRHa does not enhance the developmental capacity of xenografted oocytes. The optimal stimulation schedule for grafted tissue remains unknown.
EVALuna2:6659

Dose-Response Association of CD8+ Tumor-Infiltrating Lymphocytes and Survival Time in High-Grade Serous Ovarian Cancer - Goode, Ellen L.; Block, Matthew S.; Kalli, Kimberly R.; Vierkant, Robert A.; Chen, Wenqian; Fogarty, Zachary C.; Gentry-Maharaj, Aleksandra; Toloczko, Aleksandra; Hein, Alexander; Bouligny, Aliecia L.; Jensen, Allan; Osorio, Ana; et al. (JAMA Oncology, 2017)
Importance: Cytotoxic CD8+ tumor-infiltrating lymphocytes (TILs) participate in immune control of epithelial ovarian cancer; however, little is known about prognostic patterns of CD8+ TILs by histotype and in relation to other clinical factors. Objective: To define the prognostic role of CD8+ TILs in epithelial ovarian cancer. Design, Setting, and Participants: This was a multicenter observational, prospective survival cohort study of the Ovarian Tumor Tissue Analysis Consortium. More than 5500 patients, including 3196 with high-grade serous ovarian carcinomas (HGSOCs), were followed prospectively for over 24 650 person-years. Exposures: Following immunohistochemical analysis, CD8+ TILs were identified within the epithelial components of tumor islets. Patients were grouped based on the estimated number of CD8+ TILs per high-powered field: negative (none), low (1-2), moderate (3-19), and high (≥20). CD8+ TILs in a subset of patients were also assessed in a quantitative, uncategorized manner, and the functional form of associations with survival was assessed using penalized B-splines. Main Outcomes and Measures: Overall survival time. Results: The final sample included 5577 women; mean age at diagnosis was 58.4 years (median, 58.2 years). Among the 5 major invasive histotypes, HGSOCs showed the most infiltration. CD8+ TILs in HGSOCs were significantly associated with longer overall survival; median survival was 2.8 years for patients with no CD8+ TILs and 3.0 years, 3.8 years, and 5.1 years for patients with low, moderate, or high levels of CD8+ TILs, respectively (P value for trend = 4.2 × 10−16). A survival benefit was also observed among women with endometrioid and mucinous carcinomas, but not for those with the other histotypes. Among HGSOCs, CD8+ TILs were favorable regardless of extent of residual disease following cytoreduction, known standard treatment, and germline BRCA1 pathogenic mutation, but were not prognostic for BRCA2 mutation carriers. Evaluation of uncategorized CD8+ TIL counts showed a near-log-linear functional form. Conclusions and Relevance: This study demonstrates the histotype-specific nature of immune infiltration and provides definitive evidence for a dose-response relationship between CD8+ TILs and HGSOC survival. That the extent of infiltration is prognostic, not merely its presence or absence, suggests that understanding factors that drive infiltration will be the key to unraveling outcome heterogeneity in this cancer.
EVALuna2:34270

Endometriosis as a risk factor for ovarian or endometrial cancer - results of a hospital-based case-control study - Burghaus, Stefanie; Haeberle, Lothar; Schrauder, Michael G.; Heusinger, Katharina; Thiel, Falk; Hein, Alexander; Wachter, David; Strehl, Johanna; Hartmann, Arndt; Ekici, Arif Bülent; Renner, Stefan; Beckmann, Matthias; et al. (BMC Cancer, 2015)
No screening programs are available for ovarian or endometrial cancer. One reason for this is the low incidence of the conditions, resulting in low positive predictive values for tests, which are not very specific. One way of addressing this problem might be to use risk factors to define subpopulations with a higher incidence. The aim of this study was to investigate the extent to which a medical history of endometriosis can serve as a risk factor for ovarian or endometrial cancer.In a hospital-based case-control analysis, the cases represented patients with endometrial or ovarian cancer who were participating in studies aimed at assessing the risk for these diseases. The controls were women between the age of 40 and 85 who were invited to take part via a newspaper advertisement. A total of 289 cases and 1016 controls were included. Using logistic regression models, it was tested whether self-reported endometriosis is a predictor of case-control status in addition to age, body mass index (BMI), number of pregnancies and previous oral contraceptive (OC) use.Endometriosis was reported in 2.1 % of the controls (n = 21) and 4.8 % of the cases (n = 14). Endometriosis was a relevant predictor for case-control status in addition to other predictive factors (OR 2.63; 95 % CI, 1.28 to 5.41).This case-control study found that self-reported endometriosis may be a risk factor for endometrial or ovarian cancer in women between 40 and 85 years. There have been very few studies addressing this issue, and incorporating it into a clinical prediction model would require a more precise characterization of the risk factor of endometriosis.
EVALuna2:6731

Evidence for a time-dependent association between FOLR1 expression and survival from ovarian carcinoma: implications for clinical testing. An Ovarian Tumour Tissue Analysis consortium study - Koebel, M.; Madore, J.; Ramus, S. J.; Clarke, B. A.; Pharoah, P. D. P.; Deen, S.; Bowtell, D. D.; Odunsi, K.; Menon, U.; Morrison, C.; Lele, S.; Bshara, W.; et al. (British Journal of Cancer, 2014)
Folate receptor 1 (FOLR1) is expressed in the majority of ovarian carcinomas (OvCa), making it an attractive target for therapy. However, clinical trials testing anti-FOLR1 therapies in OvCa show mixed results and require better understanding of the prognostic relevance of FOLR1 expression. We conducted a large study evaluating FOLR1 expression with survival in different histological types of OvCa.Tissue microarrays composed of tumour samples from 2801 patients in the Ovarian Tumour Tissue Analysis (OTTA) consortium were assessed for FOLR1 expression by centralised immunohistochemistry. We estimated associations for overall (OS) and progression-free (PFS) survival using adjusted Cox regression models. High-grade serous ovarian carcinomas (HGSC) from The Cancer Genome Atlas (TCGA) were evaluated independently for association between FOLR1 mRNA upregulation and survival.FOLR1 expression ranged from 76% in HGSC to 11% in mucinous carcinomas in OTTA. For HGSC, the association between FOLR1 expression and OS changed significantly during the years following diagnosis in OTTA (Pinteraction=0.01, N=1422) and TCGA (Pinteraction=0.01, N=485). In OTTA, particularly for FIGO stage I/II tumours, patients with FOLR1-positive HGSC showed increased OS during the first 2 years only (hazard ratio=0.44, 95% confidence interval=0.20-0.96) and patients with FOLR1-positive clear cell carcinomas (CCC) showed decreased PFS independent of follow-up time (HR=1.89, 95% CI=1.10-3.25, N=259). In TCGA, FOLR1 mRNA upregulation in HGSC was also associated with increased OS during the first 2 years following diagnosis irrespective of tumour stage (HR: 0.48, 95% CI: 0.25-0.94).FOLR1-positive HGSC tumours were associated with an increased OS in the first 2 years following diagnosis. Patients with FOLR1-negative, poor prognosis HGSC would be unlikely to benefit from anti-FOLR1 therapies. In contrast, a decreased PFS interval was observed for FOLR1-positive CCC. The clinical efficacy of FOLR1-targeted interventions should therefore be evaluated according to histology, stage and time following diagnosis.
EVALuna2:6660

Expression and Regulation of Retinoic Acid Receptor Responders in the Human Placenta - Hübner, Hanna; Rascher, Wolfgang; Strick, Reiner; Kehl, Sven; Heindl, Felix; Wachter, David; Beckmann, Matthias; Fahlbusch, Fabian B.; Rübner, Matthias; Hartner, Andrea (Reproductive Sciences, 2017)
INTRODUCTION: Retinoic acid (RA) signaling through its receptors (RARA, RARB, RARG, and the retinoic X receptor RXRA) is essential for healthy placental and fetal development. An important group of genes regulated by RA are the RA receptor responders (RARRES1, 2, and 3). We set out to analyze their expression and regulation in healthy and pathologically altered placentas of preeclampsia (PE) and intrauterine growth restriction (IUGR) as well as in trophoblast cell lines. METHODS: We performed immunohistochemical staining on placental sections and analyzed gene expression by real-time polymerase chain reaction. Additionally, we performed cell culture experiments and stimulated Swan71 and Jeg-3 cells with different RA derivates and 2'-deoxy-5-azacytidine (AZA) to induce DNA demethylation. RESULTS: RARRES1, 2, and 3 and RARA, RARB, RARG, and RXRA are expressed in the extravillous part of the placenta. RARRES1, RARA, RARG, and RXRA were additionally detected in villous cytotrophoblasts. RARRES gene expression was induced via activation of RARA, RARB, and RARG in trophoblast cells. RARRES1 was overexpressed in villous trophoblasts and the syncytiotrophoblast from PE placentas, but not in IUGR without PE. Promoter methylation was detectable for RARRES1 and RARB based on their sensitivity toward AZA treatment of trophoblast cell lines. DISCUSSION: RARRES1, 2 and 3 are expressed in the functional compartments of the human placenta and can be regulated by RA. We hypothesize that the epigenetic suppression of trophoblast RARRES1 and RARB expression and the upregulation of RARRES1 in PE trophoblast cells suggest an involvement of environmental factors (eg, maternal vitamin A intake) in the pathogenesis of this pregnancy complication.
EVALuna2:34222

Expression of neuroendocrine markers in different molecular subtypes of breast carcinoma - Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Hein, Alexander; Bayer, Christian M.; Agaimy, Abbas (BioMed Research International, 2014)
Carcinomas of the breast with neuroendocrine features are incorporated in the World Health Organization classification since 2003 and include well-differentiated neuroendocrine tumors, poorly differentiated neuroendocrine carcinomas/small cell carcinomas, and invasive breast carcinomas with neuroendocrine differentiation. Neuroendocrine differentiation is known to be more common in certain low-grade histologic special types and has been shown to mainly cluster to the molecular (intrinsic) luminal A subtype.We analyzed the frequency of neuroendocrine differentiation in different molecular subtypes of breast carcinomas of no histologic special type using immunohistochemical stains with specific neuroendocrine markers (chromogranin A and synaptophysin).We found neuroendocrine differentiation in 20% of luminal B-like carcinomas using current WHO criteria (at least 50% of tumor cells positive for synaptophysin or chromogranin A). In contrast, no neuroendocrine differentiation was seen in luminal A-like, HER2 amplified and triple-negative carcinomas. Breast carcinomas with neuroendocrine differentiation presented with advanced stage disease and showed aggressive behavior.We conclude that neuroendocrine differentiation is more common than assumed in poorly differentiated luminal B-like carcinomas. Use of specific neuroendocrine markers is thus encouraged in this subtype to enhance detection of neuroendocrine differentiation and hence characterize the biological and therapeutic relevance of this finding in future studies.
EVALuna2:6612

Expression of the Immunohistochemical Markers CK5, CD117, and EGFR in Molecular Subtypes of Breast Cancer Correlated with Prognosis - Schulmeyer, Carla; Fasching, Peter; Häberle, Lothar; Meyer, Julia; Schneider, Michael; Wachter, David; Rübner, Matthias; Pöschke, Patrik; Beckmann, Matthias; Hartmann, Arndt; Erber, Ramona; Gaß, Paul (Diagnostics, 2023)
Molecular-based subclassifications of breast cancer are important for identifying treatment options and stratifying the prognosis in breast cancer. This study aimed to assess the prognosis relative to disease-free survival (DFS) and overall survival (OS) in patients with triple-negative breast cancer (TNBC) and other subtypes, using a biomarker panel including cytokeratin 5 (CK5), cluster of differentiation 117 (CD117), and epidermal growth factor receptor (EGFR). This cohort–case study included histologically confirmed breast carcinomas as cohort arm. From a total of 894 patients, 572 patients with early breast cancer, sufficient clinical data, and archived tumor tissue were included. Using the immunohistochemical markers CK5, CD117, and EGFR, two subgroups were formed: one with all three biomarkers negative (TBN) and one with at least one of those three biomarkers positive (non-TBN). There were significant differences between the two biomarker subgroups (TBN versus non-TBN) in TNBC for DFS (p = 0.04) and OS (p = 0.02), with higher survival rates (DFS and OS) in the non-TBN subgroup. In this study, we found the non-TBN subgroup of TNBC lesions with at least one positive biomarker of CK5, CD117, and/or EGFR, to be associated with longer DFS and OS.
CRIS-Team Scopus Importer:2023-02-24
Keywords: CD117; CK5; early breast cancer; EGFR; prognosis; therapy; triple-negative breast cancer

Fine needle aspiration cytology of lymph nodes in breast cancer follow-up is a feasible alternative to watchful waiting and to histology - Hammon, Matthias; Dankerl, Peter; Janka, Rolf Matthias; Wachter, David; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Uder, Michael; Wenkel, Evelyn (BMC Women's Health, 2015)
Early detection of loco-regional breast cancer recurrence improves patients' overall survival, as treatment can be initiated or active treatment can be changed. If a suspicious lymph node is diagnosed during a follow-up exam, surgical excision is often performed. The aim of this study was to evaluate the diagnostic performance of the minor invasive ultrasound-guided fine-needle aspiration cytology (FNAC) in sonomorphologically suspicious lymph nodes in breast cancer follow-up.Between April 2010 and November 2012, we performed ultrasound-guided FNAC in 38 sonographically suspicious lymph nodes of 37 breast cancer follow-up patients. Cytological specimens were evaluated if the sample material was sufficient for diagnosis and if they contained cancer cells. Patients with negative cytology were followed up clinically and sonographically. To evaluate the diagnostic performance we calculated sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for physical examination, the different sonomorphological malignancy criteria and FNAC.In 36/38 (94.7 %) lymph nodes, the pathologist had enough material to establish a final diagnosis; in 2/38 (5.3 %) lymph nodes, the probe material was non-evaluable during cytology, these 2 were excluded from further statistical evaluation. Cytology revealed malignancy in 21 lymph nodes and showed no evidence for malignancy in 15 lymph nodes. There was no evidence for malignant disease in follow-up exams in the 15 cytologically benign lymph nodes with an average follow-up time of 3 years. The diagnostic performances of physical examination and FNAC were: Sensitivity 52/100 %, specificity 88/100 %, PPV 85/100 %, NPV 60/100 %, respectively.Our preliminary results show that FNAC is a safe and fast diagnostic approach for the evaluation of suspicious lymph nodes in the follow-up of patients with breast cancer and, thus, together with follow-up represents a feasible alternative to surgery.
EVALuna2:6744

Fumarate hydratase (FH) deficiency in uterine leiomyomas: recognition by histological features versus blind immunoscreening - Siegler, Lisa; Erber, Ramona; Burghaus, Stefanie; Brodkorb, Tobias; Wachter, David; Wilkinson, Nafisa; Bolton, James; Stringfellow, Helen; Haller, Florian; Beckmann, Matthias; Hartmann, Arndt; Agaimy, Abbas (Virchows Archiv, 2018)
Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome is a rare autosomal dominant disease caused by germline mutations in the fumarate hydratase (FH) gene. Affected individuals develop cutaneous and uterine leiomyomas and aggressive RCC. To date, only few publications described the frequency and morphology of FH-deficient uterine leiomyomas. We reviewed 22 cases collected over 8 years from routine and consultation files based on distinctive histological features. In addition, we screened 580 consecutive uterine leiomyomas from 484 patients, 23 extra-uterine and 8 uterine leiomyosarcomas, and 6 leiomyomas with bizarre nuclei for FH loss using immunohistochemistry (IHC) on tissue microarrays (TMAs). All 22 FH-deficient cases were suspected on H&E sections and confirmed by FH IHC. Patients' ages ranged from 25 to 70 years (median 36). Seventeen patients had multiple nodules (2-14) measuring up to 11.8 cm. None of the patients had stigmata or family history of the HLRCC syndrome. Histologically, all FH-deficient tumors showed consistent and reproducible features as reported previously. FH loss was detected in 2/534 evaluable leiomyomas (0.4%), but in none of leiomyosarcomas. Two of six leiomyomas with bizarre nuclei were FH-deficient. FH-deficient uterine leiomyomas are rare in routine material (= 0.4%). They can be reliably identified or suspected by consistent morphological features. Our data showed predictive morphology to be superior to blind IHC screening for detecting them. The relationship of FH-deficient uterine smooth muscle tumors to the HLRCC syndrome needs further clarification.
EVALuna2:33962

HER2 and TOP2A amplification in a hospital-based cohort of breast cancer patients: associations with patient and tumor characteristics - Fasching, Peter A.; Weihbrecht, Sebastian; Haeberle, Lothar; Gasparyan, Armen; Villalobos, Ivonne E.; Ma, Yanling; Ekici, Arif Bülent; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Slamon, Dennis J.; Press, Michael F. (Breast Cancer Research and Treatment, 2014)
Gene amplification is an important factor for altered gene expression in breast cancers. TOP2A-amplification often occurs concomitantly with HER2 amplification, and it has been suggested to be predictive for the response to anthracycline chemotherapy. This study assessed the correlation between HER2 status and TOP2A co-amplification, the possible association of TOP2A single-nucleotide polymorphisms with the frequency of this co-amplification as well as confirmation of association with outcome. HER2 and TOP2A amplification were analyzed in a tissue microarray from a clinical cohort study. Additionally, a common genetic variant (rs13695) in the TOP2A gene was genotyped in germline DNA. HER2 gene amplification was compared with HER2-IHC findings assessed during clinical routine work, and the association between all the biomarkers analyzed and the clinical outcome was determined. As an exploratory aim, rs13695 genotypes were compared with TOP2A amplification status. HER2 amplification was seen in 101 of 628 (16.1 %) and TOP2A amplification in 32 (5.1 %) cancers. No TOP2A amplification occurred without HER2 co-amplification. HER2 amplification was found in 8, 13.6, and 55.1 % of patients with HER2-IHC 0/1+, 2+, and 3+ tumors, respectively. HER2-IHC was not associated with an effect on the prognosis, but HER2-FISH was. There was an association between the rs13695 genotype and TOP2A amplification status (P = 0.03). Although there was a significant correlation between HER2 status determined by IHC and HER2 by FISH, only HER2 gene amplification status by FISH was correlated with outcome indicating greater utility for FISH in routine clinical settings.
EVALuna2:6613

Hormone replacement therapy and prognosis in ovarian cancer patients - Hein, Alexander; Thiel, Falk; Bayer, Christian M.; Fasching, Peter; Häberle, Lothar; Lux, Michael P.; Renner, Stefan; Jud, Sebastian; Schrauder, Michael G.; Müller, Andreas; Wachter, David; Strehl, Johanna; et al. (European Journal of Cancer Prevention, 2013)
Estrogen exposure has at least a moderate effect on the risk for ovarian cancer, and antiestrogen therapy may be helpful in treating the disease. It is known from breast cancer that previous hormone replacement therapy (HRT) may influence the molecular profile and prognostic behavior of these tumors. The aim of this study was therefore to investigate the influence of previous HRT on the prognosis in a cohort of patients with invasive epithelial ovarian cancer. Among 547 patients who were treated for ovarian malignancies at a single institution from 1995 to 2008, a total of 244 postmenopausal patients with epithelial cancer and under the age of 75 were identified for whom information about HRT before the onset of the disease was available. HRT was correlated with tumor and patient characteristics. Analyses of overall survival and progression-free survival were carried out using Cox proportional hazards models. Age, tumor stage, and resection status correlated significantly with HRT in the univariate analysis. Patients with previous HRT were more likely to have a lower stage, to be younger, and to have optimal debulking. With regard to survival, HRT had a positive effect on overall survival, specifically in the subgroup of patients with optimal debulking. No correlation was seen in relation to progression-free survival. Sex hormone exposure through HRT may influence the behavior of ovarian cancers after the onset of the disease. This study supports the hypothesis that ovarian cancer is a hormonally influenced tumor. © 2012 Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2021-07-19
Keywords: estrogen; hormone replacement therapy; ovarian cancer; pathogenesis; prognosis

IMPAIRED GENE-EXPRESSION AND EPIGENETIC REGULATION OF RETINOIC ACID RECEPTOR RESPONDER 1 IN PREECLAMPSIA AND CHORIOCARCINOMA - Hübner, Hanna; Fahlbusch, Fabian B.; Strissel, Pamela; Strick, Reiner; Wachter, David; Beckmann, Matthias; Rübner, Matthias (2016)
EVALuna2:32961

In-situ analysis of mast cells and dendritic cells in coronary atherosclerosis in chronic kidney disease (CKD) - Wachter, David; Neureiter, D.; Campean, Valentina; Hilgers, Karl Friedrich; Buettner-Herold, M.; Daniel, Christoph; Benz, Kerstin; Amann, Kerstin Ute (Histology and Histopathology, 2018)
AIMS: Mast cells (MC) and dendritic cells (DC) have immune modulatory function and can influence T-cell activity. Both cell types have been found in atherosclerotic plaques and are thought to play an important role for plaque stability. Compared to matched segments of the non-renal population, patients with chronic kidney disease (CKD) show a more pronounced and more aggressive course of atherosclerosis with higher plaque calcification and significantly higher complications rates. It was the aim of this study to analyze the number and localization of MCs and DCs, macrophages, T- and B-cells as well as the expression of markers of inflammation such as CRP and NFκB in calcified and non-calcified atherosclerotic plaques of patients with CKD and control patients. METHODS: Fifty coronary atherosclerotic plaques from patients with endstage CKD (CKD, n=25) and control (n=25) patients were categorized according to the Stary classification and investigated using immunohistochemistry (markers for MC, DC, T, B, macrophage and NFκB). Expression was analyzed separately for the complete plaque area as well as for the different plaque subregions and correlations were analyzed. RESULTS: We found only very few DCs and MCs per lesion area with slightly increased numbers in calcified plaques. MCs per plaque area were significantly more frequent in CKD than in control patients and this was independent of plaque calcification. MCs were most frequently found in the shoulder and basis of the plaque. DCs per plaque area were significantly less in calcified plaques of CKD compared to control patients. In control, but not in CKD patients, DCs were significantly more frequent in calcified than in non-calcified plaques. Within the plaques DCs were similarly distributed between all 4 subregions. CONCLUSIONS: Coronary atherosclerotic plaques of CKD patients showed a significantly higher number of MCs whereas DCs were less frequent compared to control patients particularly if plaques were calcified. These findings might indicate a potential proinflammatory role of MCs, but not of DCs in atherosclerotic lesions of CKD patients, adding another characteristic of advanced atherosclerosis in these patients.
EVALuna2:34422

Intraparotid classical and nodular lymphocyte-predominant Hodgkin lymphoma: pattern analysis with emphasis on associated lymphadenoma-like proliferations - Agaimy, Abbas; Wild, Vanessa; Maerkl, Bruno; Wachter, David; Hartmann, Arndt; Rosenwald, Andreas; Ihrler, Stephan (American Journal of Surgical Pathology, 2015)
Most of the lymphoproliferative diseases involving the salivary glands represent indolent non-Hodgkin B-cell lymphoma (marginal zone lymphoma) related to chronic autoimmune sialadenitis (Sjögren disease). Other types of non-Hodgkin lymphomas involve the salivary glands less frequently. On rare occasions, classical Hodgkin lymphoma (CHL) and nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) present initially as a primary salivary gland mass. We analyzed a series of CHL (n=3) and NLPHL (n=6) presenting initially as parotid gland tumors concerning their pattern (parenchymal vs. intraparotid lymph node) and the presence of salivary inclusions and epithelial proliferations within the lymphoma infiltrate. The pattern of infiltration was determined on hematoxylin and eosin-stained slides assisted by immunostaining for pancytokeratin to highlight lobular salivary gland parenchyma. Patients included 6 male and 3 female individuals with a mean age of 62 years (range, 36 to 88 y). Lymphoma was localized within intraparotid lymph nodes in 8 cases and was limited to salivary parenchyma in 1 case. Parenchymal involvement in nodal-based cases was scored as absent (3) or minimal (5). Salivary inclusions (acini and ductules) within affected lymph nodes were noted in 6 cases (4/5 NLPHLs and 2/3 CHLs). In 3/6 NLPHL cases, salivary inclusions showed variable proliferative changes ranging from prominent lymphoepithelial lesions to cystic and oncocytic (Warthin-like) epithelial changes. Scanty small lymphoepithelial lesions were seen in 1 of the 3 CHL cases. One NLPHL in the intraparotid lymph node was accompanied by prominent lymphoepithelial sialadenitis in the absence of clinical signs of Sjögren disease. This study highlights that a majority of parotid gland Hodgkin lymphomas arise within intraparotid lymph nodes. Frequent entrapment and proliferation of salivary ducts and acini within the lymphoma infiltrate might mimic a variety of benign lymphoepithelial mass-forming lesions (nonsebaceous lymphadenoma, Warthin tumor, and autoimmune sialadenitis). Pancytokeratin stain is helpful for reliable assessment of the background architecture.
EVALuna2:6714

Ki67, chemotherapy response, and prognosis in breast cancer patients receiving neoadjuvant treatment - Fasching, Peter A.; Heusinger, Katharina; Haeberle, Lothar; Niklos, Melitta; Hein, Alexander; Bayer, Christian M.; Rauh, Claudia; Schulz-Wendtland, Rüdiger; Bani, Mayada; Schrauder, Michael; Kahmann, Laura; Lux, Michael P.; et al. (BMC Cancer, 2011)
Background: The pathological complete response (pCR) after neoadjuvant chemotherapy is a surrogate marker for a favorable prognosis in breast cancer patients. Factors capable of predicting a pCR, such as the proliferation marker Ki67, may therefore help improve our understanding of the drug response and its effect on the prognosis. This study investigated the predictive and prognostic value of Ki67 in patients with invasive breast cancer receiving neoadjuvant treatment for breast cancer.Methods: Ki67 was stained routinely from core biopsies in 552 patients directly after the fixation and embedding process. HER2/neu, estrogen and progesterone receptors, and grading were also assessed before treatment. These data were used to construct univariate and multivariate models for predicting pCR and prognosis. The tumors were also classified by molecular phenotype to identify subgroups in which predicting pCR and prognosis with Ki67 might be feasible.Results: Using a cut-off value of > 13% positively stained cancer cells, Ki67 was found to be an independent predictor for pCR (OR 3.5; 95% CI, 1.4, 10.1) and for overall survival (HR 8.1; 95% CI, 3.3 to 20.4) and distant disease-free survival (HR 3.2; 95% CI, 1.8 to 5.9). The mean Ki67 value was 50.6 ± 23.4% in patients with pCR. Patients without a pCR had an average of 26.7 ± 22.9% positively stained cancer cells.Conclusions: Ki67 has predictive and prognostic value and is a feasible marker for clinical practice. It independently improved the prediction of treatment response and prognosis in a group of breast cancer patients receiving neoadjuvant treatment. As mean Ki67 values in patients with a pCR were very high, cut-off values in a high range above which the prognosis may be better than in patients with lower Ki67 values may be hypothesized. Larger studies will be needed in order to investigate these findings further. © 2011 Fasching et al; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2021-07-19

Mammographic Density and Prediction of Nodal Status in Breast Cancer Patients - Hack, Carolin; Häberle, Lothar; Geisler, K.; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Fasching, Peter; Uder, Michael; Wachter, David; Jud, Sebastian; Löhberg, Christian; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: Nodal status remains one of the most important prognostic factors in breast cancer. The cellular and molecular reasons for the spread of tumor cells to the lymph nodes are not well understood and there are only few predictors in addition to tumor size and multifocality that give an insight into additional mechanisms of lymphatic spread. Aim of our study was therefore to investigate whether breast characteristics such as mammographic density (MD) add to the predictive value of the presence of lymph node metastases in patients with primary breast cancer. Methods: In this retrospective study we analyzed primary, metastasis-free breast cancer patients from one breast center for whom data on MD and staging information were available. A total of 1831 patients were included into this study. MD was assessed as percentage MD (PMD) using a semiautomated method and two readers for every patient. Multiple logistic regression analyses with nodal status as outcome were used to investigate the predictive value of PMD in addition to age, tumor size, Ki-67, estrogen receptor (ER), progesterone receptor (PR), grading, histology, and multi-focality. Results: Multifocality, tumor size, Ki-67 and grading were relevant predictors for nodal status. Adding PMD to a prediction model which included these factors did not significantly improve the prediction of nodal status (p = 0.24, likelihood ratio test). Conclusion: Nodal status could be predicted quite well with the factors multifocality, tumor size, Ki-67 and grading. PMD does not seem to play a role in the lymphatic spread of tumor cells. It could be concluded that the amount of extracellular matrix and stromal cell content of the breast which is reflected by MD does not influence the probability of malignant breast cells spreading from the primary tumor to the lymph nodes. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: breast cancer; estrogen receptor; Ki-67; mammographic density; nodal status; progesterone receptor

New prognostic and predictive markers for breast cancer - Wachter, David (Pathologe, 2016)
Breast cancer can be divided into four molecular subtypes with different prognoses using immunohistochemical markers in the routine clinicopathological work-up. The protein Ki-67 is of central importance in this context, in particular to distinguish between luminal A and luminal B carcinomas. Determination of the Ki-67 index of a carcinoma also allows a prediction of the likelihood of the response to chemotherapy. Additionally, the expression of certain cytokeratins in tumor cells is associated with a poor response to chemotherapy. The heterogeneity of molecular subtypes with regard to the histological appearance indicates an even greater diversity of breast cancer. We were able to show that a high proportion of luminal B carcinomas display neuroendocrine differentiation. Further studies with particular emphasis on histomorphological criteria should be performed to attain a more accurate classification of breast cancer and to pave the way towards targeted therapies for a better prognosis in the future.
EVALuna2:6908

Pattern of SMARCB1 (INI1) and SMARCA4 (BRG1) in poorly differentiated endometrioid adenocarcinoma of the uterus: analysis of a series with emphasis on a novel SMARCA4-deficient dedifferentiated rhabdoid variant - Strehl, Johanna D.; Wachter, David; Fiedler, Jutta; Heimerl, Engelbert; Beckmann, Matthias; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2015)
The role of the switch/sucrose nonfermenting chromatin remodeling complex in the initiation and progression of cancer is emerging. In the female genital tract, only ovarian small cell carcinoma, hypercalcemic type harbors recurrent inactivating SMARCA4 mutations. Otherwise, only rare case reports documented SMARCB1 involvement in endometrial cancer. We analyzed 24 grade 3 uterine endometrioid adenocarcinomas and 2 undifferentiated carcinomas for immunohistochemical expression of SMARCB1 and SMARCA4. All tumors showed high-grade nuclear features with a predominance of solid growth pattern. All cases showed intact nuclear SMARCB1 expression in all tumor cells. However, 1 case of a 78-year-old woman showed complete loss of SMARCA4 in 90% of the tumor with retained expression in 10% of the tumor. The SMARCA4-intact component was a moderate-to-poorly differentiated endometrioid adenocarcinoma. The SMARCA4-deficient dominating component showed solid growth of highly anaplastic undifferentiated large cells with prominent rhabdoid features. None of the 25 SMARCA4-intact cases showed rhabdoid cell morphology. To our knowledge, this is the first systematic study of SMARCB1 and SMARCA4 expression in endometrioid adenocarcinoma of uterus and the first description of a novel SMARCA4-deficient variant of dedifferentiated/undifferentiated endometrial carcinoma. The presence of a differentiated SMARCA4-intact endometrioid component points to a novel pathway of dedifferentiation in endometrioid adenocarcinoma as a consequence of a "second hit." This case further underlines the close link between the "rhabdoid phenotype" and the SWI/SNF pathway.
EVALuna2:6700

Prediction of pathological complete response and prognosis in patients with neoadjuvant treatment for triple-negative breast cancer - Gaß, Paul; Lux, Michael P.; Rauh, Claudia; Hein, Alexander; Bani, Mayada; Fießler, Cornelia; Hartmann, Arndt; Häberle, Lothar; Pretscher, Jutta; Erber, Ramona; Wachter, David; Schulz-Wendtland, Rüdiger; et al. (BMC Cancer, 2018)
BACKGROUND: It has been reported that pathological complete response is an important surrogate marker for disease-free survival and overall survival in patients with triple-negative breast cancer. This study investigates predictors of the response to neoadjuvant platinum-based or anthracycline-based treatment, and of the prognosis, in patients with triple-negative breast cancer. METHODS: A total of 121 patients with triple-negative breast cancer received neoadjuvant treatment with either platinum or anthracycline between 2008 and 2013. Pathological complete response was assessed relative to different treatments using logistic regression models with age, clinical tumor stage, grading, and Ki-67 as predictors and interaction terms, to obtain adjusted and subgroup-specific results. The impact of the pathological complete response rate on disease-free survival and overall survival was also analyzed. RESULTS: The pathological complete response rate was higher after platinum/taxane treatment compared with anthracycline/taxane (50.0% vs. 41.8%), but this was not significant in the adjusted analysis (OR 1.44; 95% CI, 0.68 to 3.09). A high histological grade (G3) was a predictor for higher pathological complete response in platinum-based therapy (OR 2.27; 95% CI, 1.00 to 5.30). The effect of neoadjuvant chemotherapy on pathological complete response was significantly different for G1-2 vs. G3 (Pinteraction = 0.013), and additional subgroup-specific differences were noted. Pathological complete response was a predictor for improved disease-free survival and overall survival in both treatment groups, with and without platinum chemotherapy. CONCLUSIONS: This retrospective study of patients with triple-negative breast cancer adds to the evidence that the treatment effect of platinum may be greatest particularly in G3 tumors. In addition, the effect of pathological complete response on the prognosis does not depend on the treatment used.
EVALuna2:34850

Prognostic relevance of Ki-67 in the primary tumor for survival after a diagnosis of distant metastasis - Loehberg, Christian R.; Almstedt, Katrin; Jud, Sebastian; Haeberle, Lothar; Fasching, Peter; Hack, Carolin; Lux, Michael P.; Thiel, Falk; Schrauder, Michael G.; Brunner, Michaela; Bayer, Christian M.; Hein, Alexander; et al. (Breast Cancer Research and Treatment, 2013)
Prediction of the prognosis for metastatic breast cancer patients depends on molecular subtypes similar to those found in patients with primary breast cancer. Several studies have shown that estrogen receptor (ER) and progesterone receptor (PR) status determine the course of the disease and the prognosis. As Ki-67 helps to differentiate molecular subtypes in patients with primary breast cancer, the aim of this study was to assess the prognostic relevance of Ki-67 in the primary tumor in relation to its prognostic relevance for patients with metastatic breast cancer. A total of 467 patients with invasive breast cancer were identified in the database of a single breast cancer center, in whom Ki-67 had been assessed in tumor material from the breast at the time of the primary diagnosis and who had developed a metastasis at any time during the subsequent course. For these patients, tumor and patient characteristics were used to determine prognostic factors relative to overall survival after the diagnosis of distant metastases. Ki-67 was added to this model to investigate whether this might improve the prediction of overall survival. In the multivariate Cox model, age at diagnosis, body mass index, nodal status, tumor size, ER and PR status, and time from diagnosis to metastasis were identified as relevant prognostic factors. Adding Ki-67 to the model improved the prediction of overall survival. There was also a significant and relevant interaction with the PR status. In patients with a low-proliferation primary tumor, a high level of PR expression would indicate an extraordinarily good prognosis (HR 0.39; 95 % CI, 0.23-0.66). In patients with higher-proliferation primary tumors, PR status was not capable of differentiating prognostic groups. Ki-67 is useful in addition to known prognostic factors for breast cancer. It is able to indicate a group of women with a poorer prognosis, specifically in the group of patients with PR-positive breast cancer. © 2013 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Ki-67; Metastatic breast cancer; Progesterone receptor; Prognosis; Proliferation

Prospective Evaluation of Acoustic Radiation Force Impulse (ARFI) Elastography and High-Frequency B-Mode Ultrasound in Compensated Patients for the Diagnosis of Liver Fibrosis/Cirrhosis in Comparison to Mini-Laparoscopic Biopsy - Pfeifer, Lukas; Zopf, Steffen; Schwitulla, Judith; Wildner, Dane; Wachter, David; Neurath, Markus; Strobel, Deike; Siebler, Jürgen (Ultraschall in der Medizin, 2015)
Purpose: Ultrasound is a well-established noninvasive test for assessing patients with liver disease. This study aims to prospectively compare ultrasound to the new technique elastography (ARFI) for the assessment of liver fibrosis/cirrhosis. Materials and Methods: High-frequency B-mode ultrasound (liver surface/vein irregularity, liver homogeneity, spleen size), ARFI quantification, mini-laparoscopic liver evaluation including biopsy were prospectively obtained in compensated patients scheduled for liver biopsy. For the diagnosis of cirrhosis, a combined gold standard (cirrhosis at histology and/or at macroscopic liver evaluation) was used. Results: Out of 157 patients, 35 patients were diagnosed cirrhotic. Ultrasound (combination of liver vein and/or surface irregularity) showed no significant difference compared to ARFI quantification for the diagnosis of significant liver fibrosis (Ishak> = 3) and cirrhosis. Diagnosis of cirrhosis had a sensitivity/specificity/PPV/NPV of 83 %(± 12) / 82 %(± 7) / 57 %(± 14) / 94 %(± 4), respectively, with ultrasound and 86 %(± 12) / 81 %(± 7) / 57 %(± 13) / 95 %(± 4), respectively, with ARFI quantification. The sensitivity/specificity/PPV/NPV for the detection of significant fibrosis were 68 %(± 13) / 86 %(± 7) / 71 %(± 13) / 84 %(± 7), respectively, for ultrasound and 70 %(± 12) / 84 %(± 7) / 69 %(± 12) / 84 %(± 7), respectively, for ARFI quantification. Conclusion: ARFI elastography and high-frequency B-mode ultrasound show similar and good results for the diagnosis of compensated liver cirrhosis and high-grade fibrosis. A key benefit of both methods is the high NPV suggesting them as noninvasive exclusion tests.
EVALuna2:2049

Sebaceous breast carcinoma: report of a rare histological special subtype - Wachter, David; Rauh, C.; Wenkel, Evelyn; Fasching, Peter; Beckmann, Matthias; Hartmann, Arndt (Pathologe, 2014)
We report on a case of sebaceous carcinoma of the breast as a rare histological special subtype of breast cancer. Because these tumors are uncommon, differential diagnostic considerations and the exclusion of Muir-Torre syndrome are emphasized. Finally possible mechanisms of development and therapeutic strategies for this carcinoma are discussed.
EVALuna2:6578

Signal decomposition for X-ray dark-field imaging - Käppler, Sebastian; Bayer, Florian; Weber, Thomas; Maier, Andreas; Anton, Gisela; Hornegger, Joachim; Beckmann, Matthias; Fasching, Peter; Hartmann, Arndt; Heindl, Felix; Michel, Thilo; Oezguel, Gueluemser; et al. (MICCAI 2014, 2014)
Grating-based X-ray dark-field imaging is a new imaging modality. It allows the visualization of structures at micrometer scale due to small-angle scattering of the X-ray beam. However, reading darkfield images is challenging as absorption and edge-diffraction effects also contribute to the dark-field signal, without adding diagnostic value. In this paper, we present a novel–and to our knowledge the first–algorithm for isolating small-angle scattering in dark-field images, which greatly improves their interpretability. To this end, our algorithm utilizes the information available from the absorption and differential phase images to identify clinically irrelevant contributions to the dark-field image. Experimental results on phantom and ex-vivo breast data promise a greatly enhanced diagnostic value of dark-field image
EVALuna2:6632

SMARCB1(INI1)-deficient sinonasal basaloid carcinoma: a novel member of the expanding family of SMARCB1-deficient neoplasms - Agaimy, Abbas; Koch, Michael; Lell, Michael; Semrau, Sabine; Dudek, Wojciech; Wachter, David; Knöll, Antje; Iro, Heinrich; Haller, Florian; Hartmann, Arndt (American Journal of Surgical Pathology, 2014)
Poorly differentiated sinonasal carcinomas are a heterogenous group of aggressive neoplasms that encompasses squamous cell carcinoma including basaloid variant, lymphoepithelial carcinoma, sinonasal undifferentiated carcinoma, and neuroendocrine-type small cell carcinoma. We herein describe 3 cases of a hitherto unreported variant combining features of basaloid carcinoma with variable intermingled rhabdoid cells. Patients were 2 women (aged 28 and 35) and a man (52 y) who presented with sinonasal masses. All had advanced local disease with bone involvement (pT4). None had a history of irradiation or a family history of rhabdoid tumors. Treatment was surgery and adjuvant chemoradiation. One patient developed liver, lung, pleural, and pericardial metastases (63 mo) and is currently (70 mo) alive under palliative treatment. Another developed recurrent cervical lymph node metastases and died of disease 8.5 years later. The youngest patient was disease-free at last follow-up 7 years later. Histologic features were very similar in all 3 cases and showed intimate admixture of compact basaloid cell nests with peripheral palisading, perivascular pseudorosettes, and a few scattered rhabdoid cells. Rhabdoid cells were more extensive in the metastasis in 1 case but formed a minor inconspicuous component in the primary tumors in all cases. Striking features common to all cases were (1) basaloid "blue" appearance at low power, (2) papilloma-like exophytic component, (3) extensive pagetoid surface growth with prominent denuding features, and (4) replacement of underlying mucous glands mimicking an inverted papilloma. Clear-cut origin from benign papilloma and overt squamous differentiation were lacking. Diffuse (2) or partial (1) p16 expression was noted, but all cases lacked human papillomavirus DNA by molecular tests. In situ hybridization was negative for Epstein-Barr virus. Immunohistochemistry showed diffuse expression of pancytokeratin. CK5 and vimentin showed intermingling of CK5/vimentin basaloid and CK5/vimentin rhabdoid cells. Complete loss of nuclear SMARCB1 expression was seen in all cases including also the denuding carcinoma in situ-like surface lesions. To our knowledge, this variant of sinonasal carcinoma has not been reported before. The identical features in all 3 cases suggest a specific disease rather than a nonspecific dedifferentiated phenotype. Awareness of this rare variant and thus reporting of additional cases is necessary for defining its full morphologic and biological spectrum.
EVALuna2:6600

The importance of pancreatic inflammation in endosonographic diagnostics of solid pancreatic masses - Vitali, Francesco; Strobel, Deike; Frulloni, Luca; Heinrich, Marc Christopher; Pfeifer, Lukas; Görtz, Rüdiger; Hundorfean, Gheorghe; Wachter, David Lukas; Wachter, David; Grützmann, Robert; Bernatik, Thomas; Neurath, Markus; et al. (Medical Ultrasonography, 2018)
AIMS: Endosonography (EUS) is one of the main diagnostic tools for the differential diagnosis of pancreatic masses. The aim of our study was to describe the value of this technique in the work-up of solid pancreatic lesions, considering the influence of the morphological evidence of pancreatic inflammation in the diagnostic process. MATERIAL AND METHODS: Retrospective analysis of prospectively collected data in our tertiary University center. From March 2007 to October 2015, 218 patients underwent EUS for a suspected solid pancreatic neoplasm (based on previous cross-sectional imaging results, idiopatic acute pancreatitis, weight loss, pancreatic hyperenzymemia, painless jaundice or elevated Ca 19-9 values). RESULTS: Malignant lesions were diagnosed in 98 (45%) patients. Sensitivity of EUS for malignancy was 91% and specificity 89.2%. Signs of pancreatic inflammation in the surrounding pancreatic parenchyma around the focal lesion were present in 97 patients (44.4%)(more often in men, smokers and drinkers, and the most common etiology was focal chronic pancreatitis) and in these patients the sensitivity and sensibility dropped to 44% and 87.1%, respectively. In patients without signs of pancreatic inflammation, the pancreatic focal lesions were adenocarcinoma, neuroendocrine tumor, ventral/dorsal split, non-pancreatic pathology, pancreatic lipomatosis and autoimmune pancreatitis. CONCLUSION: Pancreatic inflammation (either focal or involving the whole gland) lowers the diagnostic sensibility of EUS in the work- up of pancreatic masses suspected for cancer, requiring further invasive diagnostic methods. Focal autoimmune pancreatitis and paraduodenal pancreatitis are still confused with pancreatic cancer, even in the absence of pancreatic inflammation.
EVALuna2:35194

Touch Imprint Cytology and Stereotactically-Guided Core Needle Biopsy of Suspicious Breast Lesions: 15-Year Follow-up - Schulz-Wendtland, Rüdiger; Fasching, Peter; Bani, Mayada; Lux, Michael P.; Jud, Sebastian; Rauh, C.; Bayer, C.; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Uder, Michael; Löhberg, Christian (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Stereotactically-guided core needle biopsies (CNB) of breast tumours allow histological examination of the tumour without surgery. Touch imprint cytology (TIC) of CNB promises to be useful in providing same-day diagnosis for counselling purposes and for planning future surgery. Having addressed the issue of accuracy of immediate microscopic evaluation of TIC, we wanted to re-examine the usefulness of this procedure in light of the present health care climate of cost containment by incorporating the surgical 15-year follow-up data and outcome. Patients and Methods: From January until December 1996 we performed TIC in core needle biopsies of 173 breast tumours in 169 patients, consisting of 122 malignant and 51 benign tumours. Histology of core needle biopsies was proven by surgical histology in all malignant and in 5 benign tumours. Surgical breast biopsy was not performed in 46 patients with 46 benign lesions, as the histological result from the core needle biopsy and the result of the TIC were in agreement with the suspected diagnosis from the complementary breast diagnostics. A 15-year follow-up of these patients followed in 2013 and follow-up data was collected from 40 women. Results: In the 15-year follow-up of the 40 benign lesions primarily confirmed using CNB and TIC, a diagnostic sensitivity, specificity, positive and negative predictive value and accuracy of 100 % was found. Conclusion: TIC and stereotactically guided CNB showed excellent long-term follow-up in patients with benign breast lesions. The use of TIC to complement CNB can therefore provide immediate cytological diagnosis of breast lesions.
EVALuna2:6752

Trophoblast expression dynamics of the tumor suppressor gene gastrokine 2 - Fahlbusch, Fabian B.; Ruebner, Matthias; Hübner, Hanna; Volkert, Gudrun; Bartunik, Hannah; Winterfeld, Ilona; Hartner, Andrea; Menendez-Castro, Carlos; Nögel, Stephanie; Marek, Ines; Wachter, David; Schneider-Stock, Regine; et al. (Histochemistry and Cell Biology, 2015)
Gastrokines (GKNs) were originally described as stomach-specific tumor suppressor genes. Recently, we identified GKN1 in extravillous trophoblasts (EVT) of human placenta. GKN1 treatment reduced the migration of the trophoblast cell line JEG-3. GKN2 is known to inhibit the proliferation, migration and invasion of gastric cancer cells and may interact with GKN1. Recently, GKN2 was detected in the placental yolk sac of mice. We therefore aimed to further characterize placental GKN2 expression. By immunohistochemistry, healthy first-trimester placenta showed ubiquitous staining for GKN2 at its early gestational stage. At later gestational stages, a more differentiated expression pattern in EVT and villous cytotrophoblasts became evident. In healthy third-trimester placenta, only EVT retained strong GKN2 immunoreactivity. In contrast, HELLP placentas showed a tendency of increased levels of GKN2 expression with a more prominent GKN2 staining in their syncytiotrophoblast. Choriocarcinoma cell lines did not express GKN2. Besides its trophoblastic expression, we found human GKN2 in fibrotic villi, in amniotic membrane and umbilical cord. GKN2 co-localized with smooth muscle actin in villous myofibroblasts and with HLA-G and GKN1 in EVT. In the rodent placenta, GKN2 was specifically located in the spongiotrophoblast layer. Thus, the gestational age-dependent and compartment-specific expression pattern of GKN2 points to a role for placental development. The syncytial expression of GKN2 in HELLP placentas might represent a reduced state of functional differentiation of the syncytiotrophoblast. Moreover, the specific GKN2 expression in the rodent spongiotrophoblast layer (equivalent to human EVT) might suggest an important role in EVT physiology.
EVALuna2:6725

Virilizing Hilus Cell Tumor of the Ovary Associated With Efferent Ductules-like Metaplasia Within Paratubal Mesonephric Remnants - Wachter, David; Burghaus, Stefanie; Beckmann, Matthias; Agaimy, Abbas (International Journal of Gynecological Pathology, 2016)
EVALuna2:6767